Assessing children's well-being : a handbook of measures - Naar-King, Sylvie; Ellis, Deborah A.; Frey, Maureen A. (Lawrence Erlbaum Associates, 2004)
This reference guide sorts, presents and reviews all the measures that can be used to evaluate the behavioural, cognitive and emotional aspects of children's health. It organizes the measures under general headings, such as quality of life, adherence, pain management and patient satisfaction.